Mechanical determinants of faster change of direction and agility performance in female basketball athletes - Spiteri, T.; Newton, R. U.; Binetti, M.; Hart, N. H.; Sheppard, J. M.; Nimphius, S. (The Journal of Strength and Conditioning Research, 2015)
Change of direction (COD) and agility require the integration of multiple components to produce a faster performance. However, the mechanisms contributing to a faster performance without the confounding factor of athlete expertise or gender is currently unknown. Therefore, the purpose of this study was to assess body composition, strength, and kinetic profile required for a faster COD and agility performance across multiple directional changes. Six faster and 6 slower (n = 12) elite female basketball athletes completed a maximal dynamic back squat; eccentric and concentric only back squat; isometric midthigh pull; whole-body scan to determine lean, fat, and total mass; 505 COD test; T-test; and a multidirectional agility test over in-ground force plates to obtain relevant kinetic measures. Group (faster and slower) by test (2 × 3) multivariate analyses of variance with follow-up analyses of variance were conducted to examine differences between faster and slower groups and each COD and agility test (p = 0.05). Faster athletes during the 505 COD test produced significantly greater vertical force (p = 0.002) and eccentric and isometric strength capacity (p = 0.001). Faster agility and T-test athletes demonstrated significantly shorter contact times (p = 0.001), greater propulsive impulse (p = 0.02), isometric strength, and relative lean mass compared with slower athletes. Differences between faster athletes across each test seem to be attributed to the mechanical demands of the directional change, increasing force and impulse application as the degree of directional change increased. These findings indicate that different mechanical properties are required to produce a faster COD and agility performances, and the importance of a greater strength capacity to enable greater mechanical adjustment through force production and body control, during different directional changes.